Fast! - Bazaldua, Barbara; Egan, Caroline; Orpinas, Jean-Paul (New York : Golden Book, 2013)
Dusty Crophopper is a big-hearted, speed-loving crop duster who dreams of competing in the toughest and most exhilarating around-the-world air race in history.
At head of title: Disney Planes.
"From above the world of Cars"--Cover.
4-8
3.3.
Accelerated Reader AR
Keywords: Airplanes -- Fiction; Airplane racing -- Fiction